La Nueva Organización Anticomunista (NOA). Historia represiva de un escuadrón de la muerte paraestatal - López de la Torre, Carlos Fernando (CIICLA, Universidad de Costa Rica, 2018)
The article examines the history of the New Anti-Communist Organization (NOA), a parastatal death squad that existed in Guatemala between 1967 and 1968, with the main purpose of analyzing political violence and, specifically, the role it played in repression of the political dissidents of the time. In order to fulfill this purpose, a theoretical approach is proposed, which seeks to define the characteristics of the squads as repressive actors. The context and development of the repressive counterinsurgency complex that gave rise to NOA during the presidency of Julio César Méndez Montenegro (1966-1970) is then presented. Subsequently, and based on sources and specialized bibliography, the article traces the future of the organization, according to its goals, social composition, mechanisms of action, and the consequences of its crimes. The research shows how the violence of the NOA was central to the spread of terror in the late 1960s and in the development of a conservative consensus that made possible the return of the military to the presidency in 1970; reasons that highlight the importance of approaching the internal armed conflict from the study of the so-called perpetrators.